Asymptomatic bacteriuria among pregnant women attending antenatal clinic at a tertiary care centre - Basumatary, Barun K.; Dutta, Bijoy K.; Choudhury, Nabina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The term asymptomatic bacteriuria is defined as the presence of > 100,000 colonies of a single bacterial species per millilitre of urine (105 cfu /mL), cultured from clean catch midstream sample in the absence of declared symptoms. The aim of this study was to know the incidence of asymptomatic bacteriuria in pregnancy and the various factors influencing it, to identify the pathogens and their antibiotic susceptibility patterns. Methods: Clean catch mid-stream urine samples were collected from 3000 pregnant women (all trimesters) aged between 18-35 years of age attending the antenatal OPD in GMCH, Guwahati for a period of one year (July 2018-June2019). Identification of organisms and antibiotic sensitivity tests were performed as per standard methods. Results: In our study, incidence of asymptomatic bacteriuria was found to be 12.1%. Most women (52.89%) were in the age group of (20-30) years, mostly in second trimester (47.1%). Gram negative organisms were the commonest organisms isolated; among which Escherichia coli (56.75%) was the principal urinary pathogen followed by Klebsiella sp (14.33%) and Staphylococcus saprophyticus (12.67%). The isolates were most sensitive to Nitrofurantoin (87.88%). Conclusions: Asymptomatic bacteriuria is common in pregnancy. Once ASB is recognized during pregnancy, it should be appropriately treated with antibiotics and promptly followed up.